The West and the Western as grounds for reconciliation in the American Civil War - Juliette Bourdin (Revue LISA)
Focusing on a selected filmography of ten Westerns, this paper explores the reasons why Civil War films, though traditionally set in the East, eventually moved to a western setting, particularly between the early 1940s and the late 1960s. It also aims to show how and to what extent the Western genre proved to be a convenient means to sustain the tale of national reconciliation in the American Civil War. These films reveal that the genre simply drew on preexisting codes and past trends to represent both the war and Southerners, but also used what the West had to offer, notably stock enemies and a neutral territory, to bring about the national reunification.